Knowledge And Attitudes Of Nurses Towards Caring For Aids Patients In A Teaching Hospital In Nigeria - Ojo, Adeleke A.; Irinoye, Omolola O.; Akinboro, Abiodun A. (The Nigerian Journal of Pharmacy, 1996)
The knowledge, attitude and concerns of nurses regarding the care of people with AIDS in a teachng hospital were assessed with a view to determine whether or not these factors aﬂect their nursing practice. A convenient sampling technique was employed to select sixty three registered nurses from medical and surgical units who completed self administered questionnaires. Majority of nurses in the sample. (58.7%), demonstrated inadequate knowledge, 50.8% expressed negative attitude towards people with AIDS while 65.1% also expressed serious concern about their ability to provide emphatic care for patients with AIDS. Years of clinical experience did not significantly influence nurses‘ knowledge about AIDS. Similarly, I their knowledge and are ill-at ease to care for people with AIDS. Educational programmes to improve nurses knowledge of and attitude towards AIDS patients become necessary for practising nurses.